2017
DOI: 10.1590/s1679-45082017ao3913
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous breathing test in the prediction of extubation failure in the pediatric population

Abstract: Objective To assess whether the spontaneous breathing test can predict the extubation failure in pediatric population.Methods A prospective and observational study that evaluated data of inpatients at the Pediatric Intensive Care Unit between May 2011 and August 2013, receiving mechanical ventilation for at least 24 hours followed by extubation. The patients were classified in two groups: Test Group, with patients extubated after spontaneous breathing test, and Control Group, with patients extubated without sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…The SBT procedure differs with ventilator settings such as PSV, continuous positive airway pressure (CPAP), and T-piece (T-tube). Ferguson et al [ 8 ] and Nascimento et al [ 9 ] reported that the SBT did not predict extubation failure in pediatric patients on PCV because high pressure support with small endotracheal tubes overestimated the readiness for extubation. The most common cause of extubation failure was inadequate gas exchange in the lower respiratory tract problem, which suggested that performing the SBT with pressure support caused respiratory insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The SBT procedure differs with ventilator settings such as PSV, continuous positive airway pressure (CPAP), and T-piece (T-tube). Ferguson et al [ 8 ] and Nascimento et al [ 9 ] reported that the SBT did not predict extubation failure in pediatric patients on PCV because high pressure support with small endotracheal tubes overestimated the readiness for extubation. The most common cause of extubation failure was inadequate gas exchange in the lower respiratory tract problem, which suggested that performing the SBT with pressure support caused respiratory insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…20 , 21 Extubation failure is defined as reintubation or respiratory assistance needed within 48 hours of a scheduled extubation. 22 …”
Section: Methodsmentioning
confidence: 99%
“…Weaning from mechanical ventilation (MV) can be defined as the gradual reduction in respiratory support, assigning a spontaneous breathing time to let the child take responsibility for an acceptable gas exchange [3]. The term extubation failure (EF) represents a set of conditions that determine the need for reintubation and MV restoration within the first 24-72h after the removal of the endotracheal tube [3,4].…”
Section: Problem Statement and Analysis Of The Latest Researchmentioning
confidence: 99%
“…Weaning from mechanical ventilation (MV) can be defined as the gradual reduction in respiratory support, assigning a spontaneous breathing time to let the child take responsibility for an acceptable gas exchange [3]. The term extubation failure (EF) represents a set of conditions that determine the need for reintubation and MV restoration within the first 24-72h after the removal of the endotracheal tube [3,4]. Non-invasive mechanical ventilation (NIMV) offers an alternative to intubation with possibility of providing MV in the treatment of acute respiratory failure in infants and children [1] and helps restore diaphragm function as soon as possible in case of good patient-machine synchronization.…”
Section: Problem Statement and Analysis Of The Latest Researchmentioning
confidence: 99%